2012
DOI: 10.2106/jbjs.i.01575
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Lower-Limb Preservation with an Expandable Endoprosthesis After Bone Tumor Resection in Children

Abstract: Current technology does not offer a single best reconstruction option for children. Previous studies and the present series have indicated that physical and emotional functioning in patients treated with an expandable endoprosthesis are good but that complication rates remain high. Amputation and rotationplasty are alternative treatments if patients and their families are amenable to these procedures. The literature supports no single superior treatment among these three options with regard to physical or emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
52
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 54 publications
6
52
1
1
Order By: Relevance
“…To the best of our knowledge there are no published data regarding revision-free implant survival of expandable total femur replacements. Failure rates between 60% [30] and 66% [10] were reported compared with 90% in our series. However overall implant survival in those two studies was equal to our overall implant survival rate.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…To the best of our knowledge there are no published data regarding revision-free implant survival of expandable total femur replacements. Failure rates between 60% [30] and 66% [10] were reported compared with 90% in our series. However overall implant survival in those two studies was equal to our overall implant survival rate.…”
Section: Discussionsupporting
confidence: 42%
“…Reported infection rates range from 20% [11,30] to 33% [10] and aseptic loosening in 20% [30]. No dislocations of the hip with extendable total femur replacements have been reported to our knowledge.…”
Section: Discussionmentioning
confidence: 86%
“…The introduction of less-invasive expandable prostheses is purported to allow for implant expansion without further surgical interventions and without use of general anesthesia, making this type of reconstruction increasingly popular in the treatment of skeletally immature children with malignant bone tumors of the extremities [6,11,12,15,17,26,27]. However, we found that use of a particular expandable prosthesis was associated with many complications, resulting in failure of the prosthesis, inability to achieve Expandable = mini-invasive mechanically expandable prosthesis; Noninvasive expand = noninvasive expandable prosthesis; bone = segmental massive bone allograft; DAIR = débridement, antibiotics, and implant retention; EPD = epiphysiodesis; MSTS = Musculoskeletal Tumor Society; *= did not undergo lengthening.…”
Section: Discussionmentioning
confidence: 99%
“…Limb salvage surgery has replaced amputation as the first-line treatment for primary bone sarcoma of the distal femur [11,12]. This transition has been achieved without adversely affecting survival, primarily owing to improvements of chemotherapy [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…This transition has been achieved without adversely affecting survival, primarily owing to improvements of chemotherapy [11,12]. However, the complication rate after prosthetic replacement remains high.…”
Section: Discussionmentioning
confidence: 99%